Designing goals and objectives of teaching practice in the bachel or program “physics and mathematics education” in the context of learning outcomes (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article develops learning outcomes for the undergraduate educational program “Physics and Mathematics Education” on the basis of the corresponding state educational standard, the professional standard of a teaching worker (teacher, pedagogue) of a general education organization, as well as the results of a survey and interview of potential employers. Within the framework of the specified educational program, the goals and objectives of teaching practice are designed in the context of learning outcomes, which will ensure the achievement of the goals and learning outcomes of the educational program. Designing the goals and objectives of teaching practice in the context of learning outcomes contributes to the correct choice of the basis of practice.
Keywords: physics and mathematics education; educational program; learning outcomes; teaching practice; purpose of teaching practice; objectives of teaching practice